Gastrointestinal Manifestations in Diploid/Triploid Mixoploidy. Issue 6 (June 2015) - Lalani, Farida K.; Elsner, Garrett L.; Lebel, Robert Roger; Beg, Mirza B.
<x xml:space="preserve">Abstract</x> ABSTRACT A girl infant was delivered by cesarean section at 32 weeks of gestation because of growth arrest and poor movement patterns. The infant had feeding problems, which were based on gastroesophageal reflux, laryngomalacia, and decreased gut motility. Hypotonia was notable from the outset, and the patient eventually displayed significant delays in both motor and cognitive milestones. Meanwhile, lymphocytes had yielded a normal karyotype (46, XX), but at 2 years of age the patient underwent a skin biopsy and mosaicism because a 68, XX cell line was discovered in fibroblasts. At the age 6.4 years, the patient is short of stature below the 3rd percentile but has a weight at the 42nd percentile and head circumference above the 97th percentile. Other phenotypic features include low-set ears, piebald irides and scalp hair, eyelid ptosis, strabismus, broad nasal bridge, anteverted nares, upswept eyebrows, hypoplastic teeth, pectus excavatum, hypoplastic labia, scoliosis, 3–4 finger syndactyly, and 2–3 toe syndactyly. We present this case with a review of the literature for mixoploidy (the rare event of mosaicism for diploid and triploid cell lines). We add to the existing data on the clinical features of diploid/triploid mixoploidy. The complexities of the gastrointestinal problems make this case unusual.